Beyond the Crisis: Re-energizing Southeast Asian Studies - Andrew Rosser (JAS (Journal of ASEAN Studies), 2022)
This article examines the main drivers of the fiscal crisis in Asian/Southeast Asian Studies and considers ways of overcoming or at least ameliorating it. In the Australian context, several leading scholars in Asian Studies have called for various new forms of strategic state financial support to help keep the field alive, including incentives and structural support for Asian languages at both school and university levels and priority in publicly-funded research grant schemes. However, re-energizing Asian Studies in fiscal terms will undoubtedly require efforts to make the field more appealing to prospective students because of the prevalence of higher education funding models in which money follows student enrollments. This will particularly be the case with Southeast Asian Studies, given the weakness of enrollments in this sub-field. In this respect, there may be some value in seeking to create new education pathways in Asian Studies that focus on cross-national issues and problems within the region as an alternative to the traditional country-focused area studies approach